Effect of nucleation mechanism on the structure of polyfunctional calcium phosphate glass materials - Savvova, O.V.; Babich, O.V.; Shadrina, G.N. (Functional Materials, 2014)
Effect of the nucleation mechanism on structure of polyfunctional calcium silicophosphate glass materials has been studied. It has been established that the structure differentiation via liquation mechanism with formation of the nanoscale spherical nonuniformities within microbeads and consequent structure arrangement prove the ides studied materials with glass-crystalline structure during thermal treatment. Provision of fine volume crystallization of carbon-hydroxyapatite in the structure of materials with the crystal size of about 1 μm allows obtaining bioactive glass materials and coatings for bone implants with mechanical properties that allow their application on loaded areas of a bone.